2016
DOI: 10.1007/s10584-016-1665-6
|View full text |Cite
|
Sign up to set email alerts
|

Strongly increasing heat extremes in the Middle East and North Africa (MENA) in the 21st century

Abstract: The ensemble results of CMIP5 climate models that applied the RCP4.5 and RCP8.5 scenarios have been used to investigate climate change and temperature extremes in the Middle East and North Africa (MENA). Uncertainty evaluation of climate projections indicates good model agreement for temperature but much less for precipitation. Results imply that climate warming in the MENA is strongest in summer while elsewhere it is typically stronger in winter. The summertime warming extends the thermal low at the surface f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
225
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 345 publications
(237 citation statements)
references
References 66 publications
11
225
0
1
Order By: Relevance
“…Aeolian dust events blow from the Saharan desert, frequently in the form of storms in spring and autumn, and as a consequence nutrients are leached from the dust particles (Carbo et al, 2005;Herut et al, 2005). The EMS is also constantly exposed to more polluted aerosols that are influenced by domestic and industrial activities (Lelieveld et al, 2016) and usually leach higher amounts of nitrate relative to phosphorus when compared to desert dust (Herut et al, 2002;Bonnet et al, 2005). Atmospheric chemical processes, such as acidification, are mainly driven by human processes and air pollution (Seinfeld and Pandis, 1998) and significantly affect the final amount and chemical properties of the leaching procedure (Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Aeolian dust events blow from the Saharan desert, frequently in the form of storms in spring and autumn, and as a consequence nutrients are leached from the dust particles (Carbo et al, 2005;Herut et al, 2005). The EMS is also constantly exposed to more polluted aerosols that are influenced by domestic and industrial activities (Lelieveld et al, 2016) and usually leach higher amounts of nitrate relative to phosphorus when compared to desert dust (Herut et al, 2002;Bonnet et al, 2005). Atmospheric chemical processes, such as acidification, are mainly driven by human processes and air pollution (Seinfeld and Pandis, 1998) and significantly affect the final amount and chemical properties of the leaching procedure (Shi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A pronounced increase in the mean temperature is predicted throughout the entire domain with peaks of up to~2.5 C (Figure 4, top row). Furthermore, earlier GCM and RCM projections of mean seasonal temperatures in the MENA domain (e.g., Laprise et al, 2013;Lelieveld et al, 2016;Ozturk et al, 2018) have suggested that the strongest increase in mean temperature will take place in the summer season using ≥50 km resolution simulations. In spring (MAM) a west-east gradient is found showing larger temperature increases in the eastern part of the domain as compared with the western part, a trend seen also for the autumn, and partly for the winter.…”
Section: Projections Of Seasonal Mean Temperature and Precipitationmentioning
confidence: 99%
“…Future climate change projections highlight the exposure of Northwest Africa to increased heat and drought stress (Born et al, 2008;Diffenbaugh and Scherer, 2011;Lelieveld et al, 2016). This exposure underlines the need for understanding the resilience of keystone forest species such as Cedrus atlantica and the ecosystem functions they support (e.g., nutrient cycling, carbon sequestration, reducing soil erosion) in the face of global change (Parmesan, 2006;Dawson et al, 2011;Moritz and Agudo, 2013).…”
Section: Background and Rationalementioning
confidence: 99%